2015
DOI: 10.1038/bjc.2015.427
|View full text |Cite
|
Sign up to set email alerts
|

Low stromal Foxp3+ regulatory T-cell density is associated with complete response to neoadjuvant chemoradiotherapy in rectal cancer

Abstract: Background:Foxp3+ regulatory T cells (Tregs) play a vital role in preventing autoimmunity, but also suppress antitumour immune responses. Tumour infiltration by Tregs has strong prognostic significance in colorectal cancer, and accumulating evidence suggests that chemotherapy and radiotherapy efficacy has an immune-mediated component. Whether Tregs play an inhibitory role in chemoradiotherapy (CRT) response in rectal cancer remains unknown.Methods:Foxp3+, CD3+, CD4+, CD8+ and IL-17+ cell density in post-CRT su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 55 publications
5
51
0
Order By: Relevance
“…Similar results were found in a univariate analyses [7880]. McCoy et al found a low stromal T reg count to be associated with tumor regression, but not with overall survival [82]. To the best of our knowledge, this question has not been comprehensively addressed using semi-quantitative H&E based scoring such as the Klintrup-Mäkinen grade.…”
Section: Tils In Colorectal Carcinomasupporting
confidence: 60%
“…Similar results were found in a univariate analyses [7880]. McCoy et al found a low stromal T reg count to be associated with tumor regression, but not with overall survival [82]. To the best of our knowledge, this question has not been comprehensively addressed using semi-quantitative H&E based scoring such as the Klintrup-Mäkinen grade.…”
Section: Tils In Colorectal Carcinomasupporting
confidence: 60%
“…Accordingly, T reg overexpression has been considered detrimental for cancer patient survival, even though, we and others have described that a high T reg primary tumor infiltration score represents a good prognostic factor for colorectal cancer patients. 18,26,52,59 Even though our results have a major limitation in the low number of patients enrolled, we showed for the first time, to the best of our knowledge, a potential inverse correlation between PD-1 C TIL score and prostate patient bDFS. PD-1 is an inhibitory immune checkpoint receptor which is expressed on activated antigen specific CTLs during the efferent phase of the immune response.…”
Section: Discussionmentioning
confidence: 63%
“…The results of several studies have already shown that occurrence of autoimmunity, a systemic chronic inflammation profile, as well as the level of tumor infiltration by different lymphocyte subsets and macrophages, may indeed predict the outcome of patients with different disease including non small cell lung cancer (NSCLC), colorectal carcinoma (CRC), breast cancer, melanoma and other malignant diseases. [16][17][18][19][20][21][22][23][24][25] In particular, the results of previous studies by our group showed that primary tumor infiltration by immune-regulatory T cells (CD25 , namely T cm ) are associated to a prolonged PFS and OS in patients with metastatic colorectal carcinoma undergone frontline chemotherapy. [26][27][28] On these bases, we investigated whether infiltration of the primary tumor by different lymphocyte subsets may predict the outcome of PC patients.…”
Section: Introductionmentioning
confidence: 91%
“…McCoy et al evaluated the relationship of subset densities of TILs in post-nCRT surgical samples from 128 rectal cancer patients. Low stromal Foxp3+ cell density was significantly associated with pCR (adjusted odds ratio = 5.27, p = 0.006) and improved recurrence-free survival (hazard ratio = 0.46, p = 0.03) [79]. …”
Section: Molecular Biomarkers In Tumor Tissuesmentioning
confidence: 99%